The Effect of TNF-α on Regulatory T Cell Function in Graft-versus-Host Disease - Mancusi, Antonella; Piccinelli, Sara; Velardi, Andrea; Pierini, Antonio (Frontiers in Immunology, 2018)
FoxP3+ regulatory T cells (Tregs) are a subset of CD4+ T cells that can suppress proliferation and effector functions of T cells, B cells, NK cells, and antigen-presenting cells. Treg deficiency causes dramatic immunologic disease in both animal models and humans. As they are capable to suppress the function and the proliferation of conventional CD4+ and CD8+ T cells, Treg-based cell therapies are under evaluation for the treatment of various autoimmune diseases and are currently employed to prevent graft versus host disease (GvHD) in clinical trials of hematopoietic stem cell transplantation. Even though tumor necrosis factor-α (TNF-α) is well known for its pro-inflammatory role, recent studies show that it promotes Treg activation and suppressive function. In the present review, we discuss the role of TNF-α in Treg function and the possible implications on the actual treatments for immune-mediated diseases, with a particular attention to GvHD.